2022
DOI: 10.3389/fphar.2022.834947
|View full text |Cite
|
Sign up to set email alerts
|

Total Glucosides of Paeonia lactiflora for Safely Reducing Disease Activity in Systemic Lupus Erythematosus: A Systematic Review and Meta-Analysis

Abstract: Background: Total glucosides of paeony (TGP), extracted from the dried roots of Paeonia lactiflora Pall., are proven to regulate immune function in various rheumatic diseases. We aim to systematically evaluate the efficacy and safety of TGP in reducing disease activity in systemic lupus erythematosus (SLE).Methods: We searched trials in seven electronic databases and two clinical trail registries. Randomized controlled trials (RCTs) evaluating efficacy and safety of TGP for SLE were identified. The Cochrane Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Sensitivity analysis was performed to explore the source of heterogeneity by excluding articles sequentially and reading the full text. It was found that five studies (Chen, 2013;Cai et al, 2017;Yu et al, 2019;Xiang, 2020;Xu, 2020) had a significant impact on the result. The heterogeneity was reduced after excluding the five studies (I 2 = 0%, p = 0.98).…”
Section: Cumulative Dosage Of Ctxmentioning
confidence: 99%
See 4 more Smart Citations
“…Sensitivity analysis was performed to explore the source of heterogeneity by excluding articles sequentially and reading the full text. It was found that five studies (Chen, 2013;Cai et al, 2017;Yu et al, 2019;Xiang, 2020;Xu, 2020) had a significant impact on the result. The heterogeneity was reduced after excluding the five studies (I 2 = 0%, p = 0.98).…”
Section: Cumulative Dosage Of Ctxmentioning
confidence: 99%
“…A total of 18 studies reported SLEDAI as the primary outcome, including 598 patients overall in the experimental Twelve studies (Chen, 2013;Sun, 2013;Xu, 2015;Lin and Liu, 2016;Yang, 2016;Cai et al, 2017;Feng et al, 2017;Peng, 2018;Yu et al, 2019;Li and Zheng, 2020;Xiang, 2020;Xu, 2020) used TGP in combination with GC and CTX. One study (Zhao et al, 2020) used TGP in combination with GC and HCQ.…”
Section: Sledaimentioning
confidence: 99%
See 3 more Smart Citations